The Influence of the Organizational Citizenship Behavior Towards the Service Quality Performances of the Private Universities in Surabaya–Indonesia - Djati, S. Pantja (Jurnal Aplikasi Manajemen, 2011)
The purposes of this research are to analyze the influence of Organizational Citizenship Behavior towards the Service Quality performances in private universities in Surabaya, Indonesia. The population of this research is the administrative employees of 6 Private Universities in Surabaya which have over 5000 students. The sample chosen for this research are 133 employees. The research findings revealed that the Service Quality performances for student, which are delivered by the administration staffs of private universities, are good. In addition the research showed that there is a positive and significant influence of Organizational Citizenship Behavior towards the Service Quality performances. Next, there are five indicators that created the Organizational Citizenship Behavior variable; they are altruism, civic virtue, courtesy, sportsmanship and conscientiousness. Meanwhile there are four indicators that created the Service Quality variable; they are responsiveness, empathy, assurance, and reliability.Keywords: Organizational Citizenship Behavior, Service Quality Performances, OCB Indicators, Service Qualty Indicators.